Judicial Pragmatism and Legal Certainty in Determining Gāib and Mafqūd: Evidence from Mahkamah Syar’iyah Langsa - Husna, Nurul; Sufyan, Muhammad Suhaili; Sayeed, Md Mahmud Bin (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2026)
The disappearance of an heir complicates the distribution of inheritance among Muslim families. However, the absence of a clear legal framework further exacerbates this uncertainty. This study investigates legal uncertainty in determining the status of missing heirs by analyzing two decisions of the Mahkamah Syar'iyah Langsa: Number 202/Pdt.P/2025/Ms.Lgs and 243/Pdt.P/2025/Ms/lgs, which demonstrate contrasting judicial approaches. Employing a socio-legal approach, this study uses doctrinal legal analysis to examine judicial decisions and empirical data from interviews with judges, court clerks, and litigants, drawing on Roscoe Pound's distinction between law in books and law in action, as well as the theory of legal certainty. The findings reveal that although the Mahkamah Syar’iyah adopts different legal classifications—gāib in one case and mafqūd in the other—both decisions produce similar legal outcomes by preserving the inheritance rights of the missing heir. This suggests that the judicial application of mafqūd departs from its classical doctrinal foundations and reflects an adaptation to the demands of dispute resolution. More importantly, the legal classification of a missing heir creates legal certainty where social reality remains uncertain. Empirical evidence further indicates that families often perceive the missing individual as potentially alive, challenging the legal construction of mafqūd. This study argues that judicial practice prioritizes functional dispute resolution over doctrinal consistency, thereby achieving legal certainty at the expense of conceptual coherence, and highlighs the need for a clearer legal framework that better reconciles Islamic legal doctrine with the social realities of missing-heir cases.